Exploring Teaching Learning Process in Developing Higher Order Thinking Skill (HOTS) to Higher Secondary School (SMA) Students in Pontianak - Clarry Sada (STKIP Singkawang, 2019)
This study focuses on the Teaching Learning (TL) process in developing Higher Order Thinking Skill to SMA Students which is done by the secondary school teachers in Pontianak City. The National Curriculum, namely, Curriculum 2013, well known by its' abbreviation C-13, has got some significant revisions. Among those revisions, the aspect of critical thinking which emphasizes higher order thinking skill (HOTS) became the concern. The curriculum has arranged the procedures and principles of HOTS. As mentioned that the C-13 should be in line with the global competencies, thus, the teachers should understand and implement them in their teaching process. Thus, in this study, the researcher intends to explore the teachers’ knowledge and how the implementation of curriculum 2013 in the teaching-learning process. In exploring these matters, the main instrument used is questionnaires. The questionnaires contained 21 items which were focused on exploring teachers’ current knowledge about curriculum 2013, the implementation of a teaching-learning process and understood the procedures of HOTS. There were 31 English teachers as the subject of this study. The results show that (1) understand vision and mission of C-13 (73%, (2) implementing a process of HOTS (36%), (3) understand characteristics of critical thinking (55%) and (4) understand models of teaching (45%). Thus, the knowledge about C-13 with its principles on HOTS is averagely good.